Analyzing Language Dysfunctions in Patients of Motor Neuron Disease and Their Psycho-Emotional Problems: A Case Study - Azeem Alphonce; Irfan Abbas; Riaz Riaz Ullah (University of Chitral Journal of Linguistics and Literature)
Language dysfunctions and psycho-emotional problems in patients with motor neuron disease have been an underexplored area in the Pakistani context. MND patients face certain challenges based on their language, communication and psycho-emotional health that are disregarded in the context of Pakistan. This study aims to use a case study approach to investigate the language dysfunctions and psycho-emotional problems that MND patients face. This research focuses on analyzing the nature and extent of language dysfunctions and psycho-emotional problems in MND patients through the data collected from the patient and the caregivers. For data collection through observation and the caregivers' semi-structured interviews, the consent of the patient and his caregivers was taken. This data was recorded in the form of field notes which were subsequently transcribed to form textual data and identify the patterns and themes. The findings indicate that there are significant challenges that MND patients face at different phases from producing sounds in words to the formation of sentences and experiencing short and long pauses followed by muteness. Besides, it has also been found that the gradual loss of language and communicative abilities not only affects the psycho-emotional health of the patient but also the caregiver. The study contributes to the research on MND in Pakistan and draws the attention of researchers and healthcare providers to the dire need for their targeted intervention to improve patient care and support systems. The insights from this research can inform rehabilitation strategies and caregiver training programs, ultimately improving the quality of life for patients and fostering better support systems.